KREATIVITAS GURU DALAM MENYUSUN BAHAN AJAR PKn PADA PROSES PEMBELAJARAN PKn DI KELAS AKSELERASI DI SMAN 1 BANJARMASIN - Reja Fahlevi; Sapriya Sapriya (Jurnal Ilmiah Mimbar Demokrasi, 2015)
This research is motivated by the common problem a teacher usually encounters is choosing or determining the course of study which exactly suited in helping students to achieve their competence.Approach which is used in this research is qualitatively method of case of study. Observation, interviews, documentation analysis and triangulation are the process of collecting data for this research. The data is analyzed through data reduction and display, and conclusion. The result of this research shows that(1) Teacher creativity in establishing the course of study learning process in high school acceleration class at SMAN 1 Banjarmasin such as teacher’s knowledge about the course, kind of the course used in learning process and the teaching method and learning model that teachers used are good enough. (2). Factors which prevent teacher creativities course of study in civic education learning process in high school acceleration class are internal factors and eksternal factors (3) efforts that school and teachers needed to improve teacher creativities in establishing the course of study in civic education learning process in high school acceleration class at SMAN 1 Banjarmasin.